2015
DOI: 10.1155/2015/959684
|View full text |Cite
|
Sign up to set email alerts
|

IFN-CSP Inhibiting Hepatitis B Virus in HepG2.2.15 Cells Involves JAK-STAT Signal Pathway

Abstract: Frequent and high-dose administration of interferon to patients with viral hepatitis results in various side effects. In our previous study, a novel liver-targeting interferon (IFN-CSP) combining Plasmodium region I peptide with IFNα2b was successfully designed and expressed in the Escherichia coli expression systems. This targeting would target the IFNα2b specifically to the liver, thus reducing the adverse events. In the present study, we further investigated the anti-HBV effects and molecular mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…As shown in Figure 6(a) , Tyrosine phosphorylation of JAK-1 and JAK-2 was detected within 24 h and sustained for up to 72 h in human PBMC after being treated with 1 mM BA. Transcriptional activation of genes regulated by the JAK-STAT-1 pathway requires phosphorylation of tyrosine residue 701 on STAT-1 by the JAKs [ 28 , 29 ]. The tyrosine phosphorylation of JAK-1 and JAK-2 prompted us to examine the expression and phosphorylation status of STAT-1.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6(a) , Tyrosine phosphorylation of JAK-1 and JAK-2 was detected within 24 h and sustained for up to 72 h in human PBMC after being treated with 1 mM BA. Transcriptional activation of genes regulated by the JAK-STAT-1 pathway requires phosphorylation of tyrosine residue 701 on STAT-1 by the JAKs [ 28 , 29 ]. The tyrosine phosphorylation of JAK-1 and JAK-2 prompted us to examine the expression and phosphorylation status of STAT-1.…”
Section: Resultsmentioning
confidence: 99%
“…However, no significant change of IFN or IFN expression was observed following ISG15 overexpression. Although it has been reported [33] that HBV replication can be significantly suppressed in HepG2.2.15 cells with the 9-day treatment of novel livertargeting interferon 2b (IFN-CSP), our data (unpublished) showed that HBV production in HepG2.2.15 cells is not sensitive to short-period IFN 2b treatment (e.g., 24-72 h treatment), which indicated that the effects of transient ISG15 upregulation (and ISGylation) on HBV production might be independent of type I IFN. Stable transfected HepG2.2.15 cells may be employed to investigate the effect of ISG15 (and ISGylation) on type I IFN signaling pathway in future study.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that HBV DNA in the culture medium was increased by doxycycline treatment [24] or tetherin [25] overexpression while the supernatant HBsAg level was not affected. And Kinoshita W et al [26] found that host factor PRPF31 knockdown suppressed cccDNA production but showed little effect on HBcAg expression. 2) USP18 may affect HBV replication through different ways.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be a little bit different in the chronic infection. First of all, JAK-STAT Signaling Pathway has been demonstrated to be involved in regulating HBV replication in HepG2.2.15 cells [10,26] and HepAD38 cells [24,Fig. 5 USP18 upregulation inhibited IFN-induced Jak/STAT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%